Pathway for radiation therapists online advanced adapter training and credentialing. (December 2021) - Shepherd, Meegan; Graham, Siobhan; Ward, Amy; Zwart, Lisanne; Cai, Bin; Shelley, Charlotte; Booth, Jeremy
Highlights: Online Adaptive Radiation Therapy (oART) provides a solution to account for daily patient variations, but wide spread implementation is hindered by human resources and training. Physicians can mentor Radiation Therapists (RTTs) through traditional tasks such as contouring and plan approval. With evidence-based credentialing activities, decision support aids and 'on-call' caveats, RTTs can lead the oART workflow and a 'Clinician-Lite' approach. Compliance with legislative, regulatory and medico-legal governing bodies can be addressed through post-graduate study, advanced practice pathways, exemptions and delegation of task. Abstract: Online adaptive radiotherapy (oART) is an emerging advanced treatment option for cancer patients worldwide. Current oART practices using magnetic resonance (MR) and cone beam computed tomography (CBCT) based imaging are resource intensive and require physician presence, which is a barrier to widespread implementation. Global evidence demonstrates Radiation Therapists (RTTs) can lead the oART workflow with decision support tools and on 'on-call' caveats in a 'clinician-lite' approach without significantly compromising on treatment accuracy, speed or patient outcomes. With careful consideration of jurisdictional regulations and guidance from the multi-disciplinary team, RTTs can elevate beyond traditional scopes of practice. By implementing robust and evidence-based credentialing activities, they enable service sustainability and expand the real-world gains of adaptive radiotherapy to a greater number of cancer patients worldwide. This work summarises the evidence for RTT-led oART treatments and proposes a pathway for training and credentialing.